EFEKTIVITAS MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATERI PENJUMLAHAN SDN GAJAHMUNGKUR 04 - Nailis Saidah; Veryliana Purnamasari (EMTEKA: Jurnal Pendidikan Matematika, 2024)
Mastery of mathematics including problem solving at SDN Gajahmungkur 04 is low, this is achieved by obtaining low test scores on problems, the scores obtained are far below 70 or below the KKM determined by the school. This research aims to determine the effectiveness of the Problem Based Learning (PBL) model on the ability to solve addition problems in class I mathematics material at SDN Gajahmungkur 04. This type of research uses a quantitative research approach with an experimental method with a Pre-Experimental Design in the form of One Group Pretest Posttest. The sample of this research was 27 students. The results of this research are proven by the n-gain score of 0.4047 in the medium category. Then test normality with the Shapiro Wilk test on the pretest and posttest data. It can be seen from the normality test obtained, namely if the significance value is 0.074 > 0.05 then the data on the pretest is normal. Meanwhile, the posttest results were significant 0.106 > 0.05, including normal. The effectiveness test using the paired sample t-test showed that the significance value (sig.) was 0.000 or it could be said that the sig. < 0.05 (Ha accepted) which means there is a significant difference between the pretest and posttest scores. This shows the effectiveness of the problem based learning model on students' problem solving abilities. Based on the research results, it can be concluded that the problem based learning model is effective for problem solving abilities.